USING BRITISH PARLIAMENTARY DEBATE STYLE IN IMPROVING STUDENTSâ SPEAKING SKILLS - Nurhidayat, Eka (Jurnal Educatio, 2016)
Eka NurhidayatÂ English Education Department, Faculty of Teacher Training and EducationUniversity of Majalengkaekanurhidayat16@gmail.comÂ Â ABSTRACTÂ Debate is one of the methods which can be applied in class activity, especially in speaking class. It can improve the speaking ability of students by making group in discussion material given. The advantage of this method is doing together in learning activity, and demands students to give the strong arguments and also defend them. The use of British parliamentary debate style can improve students speaking skills and also requires students to express ideas in English. The aim of the research is to find out whether using British Parliamentary debate style can improve studentsâ speaking skills. The writer uses Classroom Action Research. The aim of Classroom Action Research is to improve the educational context in which the research is being carried out by using new technique. The subject of the research is taken from students debating community of LP3I Course Center Kalitanjung Cirebon. In the end of the paper, the writer tries to analyze the data as the result from individual score, observation sheet, and interview. Besides that, the researcher observes students through some questioner. After those steps, finally the writer finds that the use of British parliamentary debate style can improve studentsâ speaking skills.Â Keywords: Speaking, Debate method, British parliamentary debate style